The Political Life of Civil Law: How Power Shapes Private Legal Relations - Pramidazzura Alifa Rifqi (PT. Anagata Sembagi Education, 2025)
Civil law is doctrinally positioned as a neutral legal domain governing private relations among legal subjects. In practice, however, the formation and application of civil law are inseparable from political, economic, and institutional power relations. Legislative interventions, state policies, and judicial decisions demonstrate that civil law operates as an instrument of legal policy through which public interests are articulated and enforced within private legal relations. This article examines the political dimension of civil law and its juridical implications for private autonomy in the Indonesian legal system. Employing normative legal research with statute, conceptual, and case approaches, the study identifies normative ambiguity in positive law concerning the limits of state power over private relations, the legitimacy of using civil law as a policy tool, and the criteria for restricting private autonomy on public interest grounds. The analysis shows that such ambiguity undermines legal certainty, reduces autonomy of will, and creates the risk of unaccountable state intervention. This article argues for a normative reconstruction that treats private autonomy as a conditional principle subject to proportionate, transparent, and accountable state intervention, in order to balance individual protection with public objectives within civil law.